An Approach to Audio Description of Humour in Different Cultural Settings - López Rubio, María (Estudios de Traducción, 2024)
Audiovisual translation and, more specifically, accessibility, have a fundamental role in the multicultural world we live in. Due to cultural and social diversity, there are groups of people who depend on media accessibility services in order to consume audiovisual products because of their physical impairments, one of these services being audio description for the blind and visually impaired people (AD). The aim of this paper is to provide an approach to how humour and cultural aspects travel in audiovisual comedies, and their influence on how audio described scripts are produced in different countries. For this purpose, we will carry out a corpus analysis comparing the Spanish and the American AD versions of the original comedy film Campeones (Javier Fesser 2018) and its remake Champions (Bobby Farrelly 2023). The main findings of this descriptive study suggest that the AD practice of humorous audiovisual texts in a multicultural context is indeed a complex issue that could be addressed by Relevance Theory (Sperber & Wilson 1986), as suggested by Martínez Sierra (2009), although further research is needed.